(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
The central attention of this paper stems from my ongoing PhD journey, in which I am transitioning from being a submissive teacher to becoming a transformative mathematics teacher educator. Drawing on research studies and personal experiences, I have observed that many mathematics teachers face challenges in improving their pedagogical practices to make teaching and learning more meaningful and relevant in the Nepali context. In this scenario, the paper seeks to unpack how my identity is transfiguring from a submissive teacher to a transformative mathematics teacher educator. Autoethnography is used as the research methodology to deal with the researcher’s journey. Illeris’s transformative learning and identity theories as theoretical referents inform my study, and I have shared my experiential learning relating to a sociocultural context. The key finding of this paper is that changes in thoughts, beliefs, and actions drive identity shifts of mathematics teachers in social contexts. Additionally, this study offers insights to mathematics teachers and educators striving to transform their professional identities. In writing this paper, I have been mentored by my PhD supervisor, who acted as the critical reviewer of the ideas woven in the paper, thereby playing the second author of the paper. Although the paper is collaboratively written, it uses first-person pronouns to focus on myself as the subject of the inquiry representation.